KEMAMPUAN MENULIS CERPEN SISWA KELAS XI SMA NGERI 1 AMANUBAN TIMUR TAHUN PEMBELAJARAN 2024/2025 - Eta Endagus Nubatonis; Karus M. Margareta; Dian Sari Pekuwali (Jurnal Lazuardi, 2026)
This study aims to determine and describe the ability to write short story texts of class XI SMA Negeri 1 Amanuban Timur. The focus of this study is to escribe the ability of students to write short story texts, such as orientation, resulatation, and resulatation by emphasizing the intrinsic and intirinsic elements contained in the writing. The research method used Is a qualitative descriptive method, by collecting data through short story text analysis and povididng performance tests showing that most students are in the capable category, with a totalof 19 students, 67,89%are considered capableof writing short stories, while stdetnstwhoareinthe unablecategory number9 students,namely32,2%. Factors that in flunce the ability to write short stories include interesetand reading. Limited reading materials that can motivate stuents to write, and teaching methods applied by teachers Based on these findingis, it is recommended that teacers optimize interactive and enjoyable learning strategies and provide a veriaty of reading materials that can stimulate students intereset.it is hoped that the results of this study can serve as a reference for improving students’short story writing skills at SMA Negeri 1 Amanuban Timur. Keyword: Short story, Writing.